Features of the banking market - Shohyna, Irina; Nikitenko, Olga (My University, 2015)
Today the research of banking market - one of the fastest growing components of the global financial system and the main financial agent that satisfies the needs of the real economy and public financial resources - has become particularly relevant. Banking market is one of the most important and integral part of the modern market economy. To provide banking services, banks must have reliable background and, above all, a rather high level of assets.
Keywords: банківський ринок; ринкова економіка; banking market; market economy; банківські послуги; кафедра ділової іноземної мови та міжнародної комунікації